Radical-Scavenging Effect, Ferric Reducing Ability and Phytochemical Analysis of Urtica urens (L.) and Mercurialis annua (L.) - Doukkali Zouhra; Meryem El Jemli; Abdelhakim Bouyahya; Khang Wen Goh; Ganesh Sritheran Paneerselvam; Belatar Bahia; Yahia Cherrah; Katim Alaoui (Progress in Microbes and Molecular Biology)
Important Moroccan medicinal plants known for their food and medicinal potential include Urtica urens and Mercurialis annua. We examined the antioxidant activity of the methanolic and aqueous extracts by several in vitro systems of the assay, namely the ferric reducing/antioxidant power (FRAP) assay, the DPPH radical-scavenging activity, and the ABTS free radical-scavenging capacity. In addition, all active extracts were subjected to phytochemical screening to determine the key groups of chemicals implicated in their therapeutic activity. Total phenolic and flavonoid concentrations were also measured to see how they affected the antioxidant properties of the plant extracts. The extracts of Urtica urens and Mercurialis annua were found to have different levels of antioxidant effect in the systems tested. Based on the three different antioxidant assays, the Mercurialis annua extracts showed the highest values of antioxidant ability, based on the three used assays. Phytochemical testing of studied extracts revealed the presence of flavonoids, anthocyanins, and tannins. Total phenol and flavonoid contents were shown to provide the highest association with different antioxidant methods. The present study provides evidence that the extracts of Urtica urens and Mercurialis annua are a potential source of natural antioxidants, and this justifies their uses in Moroccan traditional medicine.